Potential of Photovoltaic on Small Stratospheric Satellite in Real-World Experiment - Pirada Techavijit; Natthapong Wongphuangfuthaworn; Polkit Sukchalerm; Aniwat Plodpai (My University, 2023)
This paper investigates the potential of monocrystalline photovoltaic (PV) panels to generate power when installed on stratospheric satellites through near-space flight experiments conducted at altitudes of 0–23 kilometers above sea level. It also compares the results with a mathematical model developed by ASHRAE in previous research, which reveals the differences caused by various factors such as atmospheric attenuation and high-level clouds. The main objective of this study is to identify the optimal altitude for deploying stratospheric satellites with appropriately sized PV panels that can generate sufficient power to meet the communication system's requirements for long-term operation.
Keywords: Spacecraft Design and Technology; Satellite Communication Systems; solar cell performance optimization